Economic growth. - Ashraf, Quamrul, 1976-; Weil, David N. (Routledge, 2025)
Why are some countries rich and others poor? This leading text introduces students to the latest theoretical tools, data, and insights underlying this pivotal question. By showing how empirical evidence relates to new and old theoretical ideas, 'Economic Growth' provides students with a complete introduction to the discipline and the latest research.